2010
DOI: 10.1002/cncr.25624
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ovarian cancer screening decision model that incorporates disease heterogeneity

Abstract: BACKGROUND: Pathologic and genetic data suggest that epithelial ovarian cancer may consist of indolent and aggressive phenotypes. The objective of the current study was to estimate the impact of a 2-phenotype paradigm of epithelial ovarian cancer on the mortality reduction achievable using available screening technologies. METHODS:The authors modified a Markov model of ovarian cancer natural history (the 1-phenotype model) to incorporate aggressive and indolent phenotypes (the 2-phenotype model) based on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
3
24
0
2
Order By: Relevance
“…They found that annual screening had the potential to result in up to a 43% reduction in ovarian cancer mortality but at an incremental cost of $73,500 per year of life saved in the general population (or $36,000 in the high-risk population). A follow-up study [11] which separated ovarian cancer cases into two phenotypes found less benefit from annual screening since a large percentage of the early-stage detections occurred for the less aggressive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…They found that annual screening had the potential to result in up to a 43% reduction in ovarian cancer mortality but at an incremental cost of $73,500 per year of life saved in the general population (or $36,000 in the high-risk population). A follow-up study [11] which separated ovarian cancer cases into two phenotypes found less benefit from annual screening since a large percentage of the early-stage detections occurred for the less aggressive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that ovarian cancer screening detects more indolent and less aggressive Type 1 cancers [45] and that the frequency of Type 2 cancer is ~75% is higher than Type 1 with higher mortality rate for Type 2 cancer due to its faster rate of growth and metastasis. This result is in contrast to findings from the Kentucky Ovarian Cancer Screening trial where 83.3% of early stage malignancies were aggressive Type 2 cancers [5,35,36,38].…”
Section: Type 1 and Type 2 Ovarian Cancers Found In Ultrasound Imamentioning
confidence: 99%
“…При использовании протеомных методов поиска биомаркеров A-SAA был выявлен как один из потен-циальных биомаркеров РЯ [48], рака легких [49], по-чки [50], носоглотки [51].…”
Section: ж е н с к о й р е п р о д у к т и в н о й с и с т е м ы 1 ' unclassified
“…A-SAA был идентифицирован в качестве маркера метастазирования аденокарциномы простаты в кост-ную ткань [48]. Для рака легкого показано прогресси-рующее увеличение концентрации A-SAA с прогрес-сированием рака.…”
Section: ж е н с к о й р е п р о д у к т и в н о й с и с т е м ы 1 ' unclassified